Density, Division and Distance: Understanding China’s Urban Land-Use Change from an Economic Geography Perspective - Gao, Xing; Zhu, Jin; Liu, Jiayao (Applied spatial analysis and policy, 2024)
Although land-use change driven by general economic factors has been discussed substantially, rarely has any work been done within the perspective of economic geography – considering the impact of economic spatial differences. This study applies the 3Ds (Density, Division and Distance) framework published by the World Bank to explore their impacts on urban land-use change – focusing on urban land and stand-alone industrial land. Employing the dynamic system-GMM (Generalized Method of Moments) model and a mediating effect model, we examine the direct and indirect effects of 3Ds on land-use change in cities with different income levels and in different regions. Our results find that deepening spatial differences facilitate the expansion of urban land and stand-alone industrial land use. Furthermore, the 3Ds has indirect effects on land use through the interactions between density and distance, as well as between division and distance. These impacts are divergent in cities with different income levels and region-specific. The main contribution of this paper is twofold. Theoretically, the study develops a new systematic framework to explain land-use change within the field of economic geography. Empirically, we examine the theoretical framework of spatial inequality by considering both direct and indirect effects. This study also has important policy implications for improving the economic value of land use.